An Investigation of Perceptual, Verbal, and Non-Verbal Barriers in the Workplace - Ghani, Madaha Hanafi @ Mohd; Zamani, Nur Fadzilah Muhamad; Azram, Aina Athirah Rozman; Rahmat, Noor Hanim; Omar, Siti Khadijah; Sharif, Nurshaza Farah Md (International Journal of Asian Social Science, 2022)
Effective communication creates a positive working environment and thus increases the job performance of the staff. However, the absence of proper communication between the members of an organisation or a company would result in failure to achieve the agreement while working. Therefore, this study aims to investigate how perceptual factors, verbal, and non-verbal communication can be barriers to effective communication in the workplace. A set of questionnaires is used and distributed to workers of various industries in different companies. It consists of five parts: the demographic profile, verbal communication, non-verbal communication, work environment, and organisational values. A total of ninety-four (94) responses are received and recorded. Findings reveal how perceptual, verbal, and non-verbal factors influence the flow of communication in the workplace. Consequently, the findings of this study can help employers and employees to improve communication at all levels for the betterment of the work performance of all workers.